The reduction of ship-based emissions: aggregated impact on costs and emissions for North Europe-East Asia liner services. (1st January 2014) - Doudnikoff, Marjorie; Gouvernal, Elisabeth; Lacoste, Romuald
This paper investigates the aggregated impacts of future environmental policies aimed at abating atmospheric emissions from ships. These policies include the low-sulphur fuel requirements from Annex VI of MARPOL and a European market-based instrument on CO2 emissions. Two regulatory scenarios are proposed as well as a cost model for liner services on the North Europe-East Asia trade for the period 2015 to 2025. This paper assesses the cumulated cost implications of sulphur and CO2 policies for a typical North Europe-East Asia loop. This provides an economic assessment of the aggregated effect of sulphur and CO2 policies at the shipping lines' level. In addition, an analysis on the indirect environmental impact of these policies is carried out. We show that the policy on sulphur emissions from ships may have a significant effect on CO2 emissions. The results of this paper, both from the economic and environmental analyses, argue for a holistic approach when regulating vessel-based emissions.